2000
DOI: 10.1074/jbc.m004703200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of p22 Is Mediated by Phospholipase D-dependent and -independent Mechanisms

Abstract: Human neutrophils participate in the host innate immune response, partly mediated by the multicomponent superoxide-generating enzyme NADPH oxidase. A correlation between phosphorylation of cytosolic NADPH oxidase components and enzyme activation has been identified but is not well understood. We previously showed that p22 phox , the small subunit of the membranebound oxidase component flavocytochrome b 558 , is an in vitro substrate for both a phosphatidic acid-activated kinase and conventional protein kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 80 publications
5
50
1
2
Order By: Relevance
“…In addition, PMA stimulates translocation of p47 PHOX , p67 PHOX , and Rac1 to membranes (19). fMLP, on the other hand, was reported to activate phospholipase D (PLD) through receptor to form phosphatidic acid (PA), which in turn stimulates PA-activated protein kinase, resulting in activation of p22 PHOX by phosphorylation (54). PLD induced superoxide formation in J774 cells, and Tat-C3 did not inhibit it (data not shown), suggesting that Rho is not involved in the signaling pathway via PLD to activate NADPH oxidase.…”
Section: Rho Is Involved In Superoxide Formation By Macrophages-mentioning
confidence: 94%
“…In addition, PMA stimulates translocation of p47 PHOX , p67 PHOX , and Rac1 to membranes (19). fMLP, on the other hand, was reported to activate phospholipase D (PLD) through receptor to form phosphatidic acid (PA), which in turn stimulates PA-activated protein kinase, resulting in activation of p22 PHOX by phosphorylation (54). PLD induced superoxide formation in J774 cells, and Tat-C3 did not inhibit it (data not shown), suggesting that Rho is not involved in the signaling pathway via PLD to activate NADPH oxidase.…”
Section: Rho Is Involved In Superoxide Formation By Macrophages-mentioning
confidence: 94%
“…It has been shown that p22 PHOX can be phosphorylated through phospholipase D (PLD), suggesting that PLD activity is required for superoxide formation (Regier et al, 2000). Involvement of PLD was further evidenced by that the activation of PLD is tightly coupled to the phagocytosis of opsonized zymosan by human macrophages (Kusner et al, 1996) and RhoA is an activator of PLD activity (Malcolm et al, 1994).…”
Section: Regulatory Proteins Involved In Superoxide Form Ationmentioning
confidence: 99%
“…We found that the addition of exogenous PLD to the macrophages induced the enhancement of the superoxide formation (results not shown), suggesting that PLD activity is required for the superoxide formation. It has been shown that p22 PHOX can be phosphorylated through PLD, suggesting that PLD activity is required for the superoxide formation (Regier et al, 2000). Moreover, the activation of PLD is tightly coupled to the phagocytosis of opsonized zymosan by human macrophages (Fallman et al, 1993;Kusner et al, 1996).…”
Section: Mechanism For the Superoxide Formation Mediated Through Rho mentioning
confidence: 99%